The approach between academics and journalists through the use of ethnographic methods - Borges, Fernando (2014)
One of the challenges of the studies in the Field of Communication is the coming together between the academic world and the professional world. This relationship can be increased through an empiric work based on ethnographic methods. The use of this kind of methodology is based on the participant observation and interview make possible an analysis of the micro social realities, improving the understanding of the daily routines, the bureaucratic structure, inside competition, professional ideologies, relationship with the sources and cultural practices in the world of journalism, highlighting the role of individual action in the social structure. This work pays special attention to the Interview as a method of qualitative research and poses some questions about the neutrality and the relationship it creates between the researcher and the journalist. In order to produce good results it is necessary that the researcher minimizes the differences between then, creating an environment of trust, reducing the risks of symbolic violence, making easy the understanding and the data collection. If the researcher is able to accomplish these conditions, he will establish a relationship with the journalist capable of creating dialectic knowledge -enhanced by the reflexivity of the journalists - that will create good research results and it will strengthen relations between the academic and journalistic worlds.